Eksperimentasi Model Pembelajaran Kooperatif Tipe Two Stay Two Stray dengan Assessment For Learning Terhadap Prestasi Belajar Matematiksa Ditinjau dari Gaya Belajar Siswa - Ellen Proborini; Swapaka Listya Trusthi (Universitas Sarjanawiyata Tamansiswa, 2021)
The research’s objective was to know the learning model’s effects on learning achievement viewed form student learning styles. The learning models compared were Two Stay Two Stray using assessment for learning and direct learning. The research’s population was grade XI students of SMK Tunas Harapan Pati year 2020/2021. This study used experimental research method with quasi experimental research. The data collection techniques used documentation, test, and questionnaire method. Hypothesis testing used a two-way variance analysis. The research results are: 1. Students subjected to the two stay two stray assessment for learning model have better learning achievement than students subjected to two stay two stray and Direct learning. 2. Students with auditory learning styles have better learning achievement than students with visual and kinesthetic learning styles. 3. There is an interaction between the Two Stay Two Stray assessment for learning, Two Stay Two Stray, and Direct learning models viewed from student learning styles on student achievement in class XI SMK Tunas Harapan Pati on the opportunity material.